Peran Gender Diversitas dalam Meningkatkan Kolaborasi Komite Audit dan Kepemilikan Manajer Terkait Kinerja Lingkungan: Audit - Putri, Sherin Kristina; Anggraini, Melisa (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
Environmental performance has become a focus for investors because it reflects the company's responsibility towards the natural ecosystem and its surroundings. Environmental performance has become one of the components that influences investment decisions. One of the components that influences environmental performance is governance and gender diversity. This study examines the role of gender diversity in strengthening the relationship between the audit committee and managerial ownership on the company's environmental performance. This study covers all companies from various sectors listed on Bloomberg in 2015 - 2022. The analysis method used in this study uses a quantitative method using secondary data. The results of the study indicate that management ownership significantly affects social and environmental performance. In addition, gender diversity will strengthen the relationship between managerial ownership and environmental performance. These findings highlight the importance of women's inclusion in supervisory and managerial positions to improve the company's environmental responsibility. Thus, this study makes an important contribution to the literature on corporate governance and environmental performance, as well as providing practical implications for companies and policy makers in developing strategies to improve environmental sustainability through gender diversity.